Multiwavelength monitoring of the gravitationally lensed blazar QSO B0218+357 between 2016 and 2020 - de Palma F.; D'Ammando F.; Barnacka A.; Hada K.; Sahu D.K.; Lähteenmäki A.; Acciari V.A.; Ansoldi S.; Antonelli L.A.; Arbet Engels A.; Artero M.; Asano K.; et al. (Italy, 2025)
QSO B0218+357 is currently the only gravitationally lensed source from which very-high-energy (VHE, &100GeV) gamma-ray emission has been detected. We report the multiwavelength monitoring observations of this source performed between 2016 and 2020 in radio interferometry, optical, X-ray and gamma-ray bands. During the monitoring individual flares and hints of enhanced states in optical, X-ray and GeV bands have been observed, and the simultaneous data taken by the MAGIC telescopes allow us to search for the VHE gamma-ray emission associated with these events.
37th International Cosmic Ray Conference (ICRC2021)